Avaliação físico-mecânica de compósitos cimentícios reforçados com partículas de papel kraft reaproveitadas in loco - Soares, Marcello Martins (2022)
Civil construction is one of the dietary activities that generate the most waste, and most of it is discarded organically, causing environmental effects. One of the wastes generated in almost all civil construction works, and in large volumes, is cement packaging. The packaging is made of Kraft paper, from pulps of long cellulosic fibers, which have good physical and mechanical properties. This research aims to evaluate the addition of kraft paper fibers from cement bags in coating mortar. The search for the use of renewable resources to reduce the negative effects caused by the allocation of this result was associated with the need to find solutions to reduce the incidence of cracks in a given coating mortar. In this investigation, coating mortars were developed using Portland cement, with substitutions of 0.5%, 1.0% and 1.5% of a pre-mass composed of limestone and hydrated lime with kraft paper fibers from sacks of cement bags. The physical and mechanical properties of the composites, scanning electron microscopy (SEM) analysis, calorimetry analysis, and evaluation of the application and finish of the coating were evaluated. Among the compositions studied, the mix with 0.5% Kraft paper fibers in the test specimens administered performed well and promoted the reduction of cracks. The proposal becomes viable, considering the results obtained, reduction of environmental impacts and savings in materials.